Engagement et désengagement dans les paratextes des traductions théâtrales du XVIe siècle - Daniele Speziari (Revue Italienne d'Etudes Françaises)
This essay examines the paratexts (such as prefaces, dedicatory epistles, forewords, and more) of several drama translations that were published in France during the 16th century, in order to prove that, even though most of these texts were engaged and composed with didactic and pedagogical aims in mind, disengagement was not unheard of in this domain and was actually at the heart of the work of some translators. By rejecting the notion of translation as service, they were pursuing their own individual “profit” and locking themselves in an “ivory tower” which embodied either a lack of ambition or a strong ambition of experimenting with language and standing out as a pioneer.